Teologi New Apostolic Reformation dan Pandemi Covid 19 - Heppy Yohanes; Yonatan Alex Arifianto (Jurnal Salvation, 2021)
Abstract: The COVID-19 pandemic that has swept across the country has made a shift in all fields, especially the church. This shift requires the church to make significant changes. Many churches appear unprepared for the changes required and congregations are seen to be confused and not growing. The New Apostolic Reformation (NAR) theology that developed from 2001 provides many teaching concepts as a continuation of the wave of the Pentecostal movement in the world. The concept of NAR theology which consists of five ministries, the mandate of seven mountains, dominion theology, the Gospel of the Kingdom can provide fresh air to answer the problems that occur in the church in answering all its problems. In order to provide a clear and precise review, the researcher applied a qualitative descriptive research method with a literature study. The discussion carried out was not only limited to theological concepts, but also the application of the theological concept of NAR to answer the problem of the COVID-19 pandemic, as well as discussing the problems of many parties' questions regarding prophecy that did not occur from this NAR group.   Abstrak: Pandemi Covid 19 yang melanda seluruh negara membuat pergeseran terjadi di seluruh bidang, khususnya gereja. Pergeseran ini menuntut gereja untuk melakukan perubahan yang signifikan. Banyak gereja yang terlihat tidak siap atas perubahan yang dituntut dan terlihat jemaat yang kebingungan dan tidak bertumbuh. Teologi New Apostolic Reformation (NAR) yang berkembang dari tahun 2001 memberikan banyak konsep pengajaran sebagai kelanjutan dari gelombang gerakan pentakosta di dunia. Konsep teologi NAR yang terdiri dari lima jawatan, mandat tujuh gunung, teologi dominion, Injil Kerajaan dapat memberikan angin segar untuk menjawab permasalahan yang terjadi atas gereja dalam menjawab seluruh persoalannya. Agar dapat memberikan ulasan yang jelas dan tepat, peneliti menerapkan metode penelitian deskriptif kualitatif dengan studi kepustakaan. Pembahasan yang dilakukan tidak hanya sebatas konsep teologi saja, namun penerapan konsep teologi NAR untuk menjawab masalah pandemi covid 19, serta membahas problematika tentang pertanyaan banyak pihak mengenai nubuatan yang tidak terjadi dari kelompok NAR ini.